Evaluation Gene Expression of Long Non-coding RNA and 5-Hydroxytriptamine 3A Receptor in Bronchial Asthma - Mubark, Nawras; Shahadha, Mohammed Abd Ali; Abbas, Ihab Majeed (Journal of Biomedicine and Biochemistry, 2024)
Background Bronchial asthma is a reversible chronic inflammatory condition of the airways. It is a complex clinical syndrome characterized by airway congestion, inflammation, and hypersensitivity to numerous stim- uli. IncRNAs and the serotonin receptors, named 5-Hydroxytriptamine 3A Receptor (5-HT3A), causes the release of a number of pro-inflammatory cytokines that are crucial in allergic asthma.Aim Present study aimed to evaluate role of gene expression of IncRNA (and 5-HT3A in asthma.Methods In this study, 100 people with bronchial asthma (59 women and 41 men) between the ages of 2 and 61 were compared to 30 healthy people of the same age range (14 women and 16 men).Results current results showed a significant correlation (p